The sightseeing attractions of Wrocław and their potential exploitation - Wyrzykowski, Jerzy (Turyzm/Tourism, 2009)
The article presents the more important results of research concerning the sightseeing attractions of Wrocław which can then be used to inform the organisation of the tourism offer of the city.